menu
Perfect! \(\vec{A} = -2\hat{i} - 5\hat{j}\) and \(\vec{B} = -8\hat{i} + 3\hat{j}\) For \(\vec{A} - \vec{B}\), you need to subtract the x- and the y-components separately. The x-component will be \(-2-\left(-8\right) = 6\) and the y-component will be \(-5-\left(+3\right) = -8\).
If \(\vec{A} = 5\hat{i} + 4\hat{j}\), \(\vec{B} = 3\hat{i} + 7\hat{j}\) and \(\vec{C} = 2 \hat{i} + 12 \hat{j}\), what is \(\vec{A} + \vec{B} - \vec{C}\)?
  • \(10\hat{i} + 23\hat{j}\)
  • \(6\hat{i} - 1\hat{j}\)
  • \(-10\hat{i} + 23\hat{j}\)
  • \(-6\hat{i} + 1\hat{j}\)